Anti-packet-loss joint encoding for voice-over-IP steganography - Zhan-zhan GAO; Guang-ming TANG; Wei-wei ZHANG (Tongxin xuebao)
VoIP (voice over IP) is a kind of voice communication technology based on UDP/IP protocols. Packet loss will inevitably happen when the channel environment deteriorates, which can pose challenges to the reliable transmission of VoIP steganography. A steganographic model based on joint encoding was proposed. In this model, packet erasure coding was introduced to preprocess the secret data. And the encoded data were embedded into voice packets with minimum dis-tortion using matrix embedding. Furthermore, the influences of key parameters on the performance of joint coding were studied. The selection algorithm for optimal parameters was also given. Experimental results show that the proposed joint coding can effectively improve steganographic resistance to packet loss, and decrease the number of modifications to the voice stream.